2020
DOI: 10.1103/physrevaccelbeams.23.084801
|View full text |Cite
|
Sign up to set email alerts
|

High-gradient testing of an S -band, normal-conducting low phase velocity accelerating structure

Abstract: A novel high-gradient accelerating structure with low phase velocity, v=c ¼ 0.38, has been designed, manufactured and high-power tested. The structure was designed and built using the methodology and technology developed for CLIC 100 MV=m high-gradient accelerating structures, which have speed of light phase velocity, but adapts them to a structure for nonrelativistic particles. The parameters of the structure were optimized for the compact proton therapy linac project, and specifically to 76 MeV energy proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…High gradient testing of accelerating structures operating at X-band is routinely conducted at SLAC National Accelerator Laboratory demonstrating peak surface electric fields greater than 350 MV/m for 1×10 −4 to 1×10 −2 BDR(1/pulse/meter) for RF pulse length of 85-300 ns [12][13][14]. This is similar with testing of X-band structures at CERN/KEK [22] and S-band work form CERN [23] with both showing a maximum achievable surface electric field of 225 MV/m for a BDR of less than 1×10 −7 (1/pulse/meter) for the 250 ns pulse length at X-band and surface field of 220 MV/m for a BDR of less than 1×10 −6 (1/pulse/meter) for the 1.2 µs pulse length at S-band. Those same X-band (11.424 GHz) experiments showed that the breakdown rate correlates with peak pulse surface heating.…”
mentioning
confidence: 52%
“…High gradient testing of accelerating structures operating at X-band is routinely conducted at SLAC National Accelerator Laboratory demonstrating peak surface electric fields greater than 350 MV/m for 1×10 −4 to 1×10 −2 BDR(1/pulse/meter) for RF pulse length of 85-300 ns [12][13][14]. This is similar with testing of X-band structures at CERN/KEK [22] and S-band work form CERN [23] with both showing a maximum achievable surface electric field of 225 MV/m for a BDR of less than 1×10 −7 (1/pulse/meter) for the 250 ns pulse length at X-band and surface field of 220 MV/m for a BDR of less than 1×10 −6 (1/pulse/meter) for the 1.2 µs pulse length at S-band. Those same X-band (11.424 GHz) experiments showed that the breakdown rate correlates with peak pulse surface heating.…”
mentioning
confidence: 52%
“…Fig. 2: Cross-section of a rendering of a constituent disk showing the channels for the brazing alloy (1) and the integrated cooling channels (2). One half of an RF cell is present on each side of the central portion of disk (shown in the close-up).…”
Section: Mechanical Design Fabrication and Assemblymentioning
confidence: 99%
“…To date, over twenty prototype X-band (12 GHz) accelerating structures have reached unloaded accelerating gradients of 100 MV/m during testing [2][3][4][5] and recently, high-gradient X-band technology has also found use in other applications including free electron lasers (FELs) [6,7], radiation therapy [8,9], and inverse Compton scattering (ICS) sources [10]. Typically, individual precision machined disks are stacked and diffusion bonded to form the multi-cell accelerating sections on the CLIC structures [11].…”
mentioning
confidence: 99%
“…Advances in understanding limitations on accelerating gradients go beyond linear colliders. Accelerators are used in applications such as inverse Compton scattering gamma ray sources [5,6], compact free-electron lasers (FELs) [34][35][36], and compact medical linacs for hadron therapy [37][38][39][40][41][42].…”
Section: Overview Of High-gradient Studies For Particle Acceleratorsmentioning
confidence: 99%